Intrathecal resiniferatoxin in a dog model: efficacy in bone cancer pain. Issue 6 (June 2015) - Brown, Dorothy C.; Agnello, Kimberly; Iadarola, Michael J.
Abstract : Abstract: Resiniferatoxin (RTX) is the most potent among all known endogenous and synthetic agonists for the transient receptor potential vanilloid 1 (TRPV1) receptor, which is a calcium-permeable nonselective cation channel, expressed on the peripheral and central terminals of small-diameter sensory neurons. Prolonged calcium influx induced by RTX causes cytotoxicity and death of only those sensory neurons that express the TRPV1 ion channel leading to selective targeting and permanent deletion of the TRPV1-expressing C-fiber neuronal cell bodies in the dorsal root ganglia. The goal of this project was to provide preclinical efficacy data, that intrathecal RTX could provide effective pain relief and improve function in dogs with bone cancer without significant long-term side effects. In a single-blind, controlled study, 72 companion dogs with bone cancer pain were randomized to standard of care analgesic therapy alone (control, n = 36) or 1.2 μg/kg intrathecal RTX in addition to standard of care analgesic therapy (treated, n = 36). Significantly more dogs in the control group (78%) required unblinding and adjustment in analgesic protocol or euthanasia within 6 weeks of randomization, than dogs that were treated with RTX (50%; P < 0.03); and overall, dogs in the control group required unblinding significantly sooner than dogs that had been treated with RTX ( P < 0.02). The analgesic effect was documented in these dogs without any evidence of development of deafferentation pain syndrome that can be seen with neurolytic therapies. Abstract : Supplemental Digital Content is Available in the Text.Intrathecal resiniferatoxin provides effective pain relief in a naturally occurring canine bone cancer model without occurrence of self-mutilation, which can be indicative of deafferentation pain.